(untitled) (Journal of Business Management and Accounting, 2019)
Small and medium enterprises (SMEs) are playing an increasingly important role in sustaining economic growth and logistic system in Malaysia. The objective of this study is to investigate the relationship between technology, financial and location strategy and customer relationship management performance. The population of this study consist of customers of three logistic companies in Penang, Selangor and Johor Bharu. Simple random sampling method was used from the target population. A total of 391 respondents consisting of individuals who are consumers of the logistic services offered by the companies answered the questionnaires. Findings from the study has important managerial implications as it will enable management of SMEs to understand the progressive and highly varied CRMP practices and contextual factors that contribute to CRMP as well as effective, efficient and innovative implementation. The study concludes that customer satisfaction is a significant component of CRMP.